2019
DOI: 10.1002/jms.4429
|View full text |Cite
|
Sign up to set email alerts
|

Vibrating tip spray ionization mass spectrometry for direct sample analysis

Abstract: In this work, a vibrating tip spray ionization source was developed for direct mass spectrometric analysis of raw samples under voltage-free condition. A solid tip was mounted on a vibrator, and the solid tip was placed on the front of MS inlet. Liquid, viscous, and bulk solid samples could be directly loaded on the tip-end surface, and then a drop of solvent at microliter level was subsequently loaded on the tip for dissolution and extraction of analytes, and a vibrator was then started to atomize and ionize … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…More specifically, Goodlett and co-workers have suggested that SAWN may be an improved technique to study native protein complexes under lower internal energy conditions. Additionally, similar techniques that utilized vibrations to achieve atomization and ionization have shown that the noncovalently bound heme can be retained by holomyoglobin under native MS conditions …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More specifically, Goodlett and co-workers have suggested that SAWN may be an improved technique to study native protein complexes under lower internal energy conditions. Additionally, similar techniques that utilized vibrations to achieve atomization and ionization have shown that the noncovalently bound heme can be retained by holomyoglobin under native MS conditions …”
Section: Introductionmentioning
confidence: 99%
“…Additionally, similar techniques that utilized vibrations to achieve atomization and ionization have shown that the noncovalently bound heme can be retained by holomyoglobin under native MS conditions. 26 UASI, AMUSE, and SAWN all directly atomize sample using a piezoelectric resonator process. The mechanical energy is used to make microdroplets that result in ion formation.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Existing acoustics-based methods generate droplets from liquid on a vibrating substrate for ionization. [46][47][48] For VSSI, we have demonstrated two working modes: on-substrate ionization and touch ionization. The touch ionization mode is directly compatible with the solvent extraction based workflow, and it can thus be a convenient method for direct surface MS analysis because of its simplicity and flexibility.…”
Section: Trimpin Et Al Reported Matrix-assisted Ionization a Techniqmentioning
confidence: 99%
“…Recently, we reported a new mechanical vibration–based ionization method termed vibrating sharp‐edge spray ionization (VSSI) 44,45 in which liquid samples are nebulized at the sharp edges of a vibrating glass slide. Existing acoustics‐based methods generate droplets from liquid on a vibrating substrate for ionization 46–48 . For VSSI, we have demonstrated two working modes: on‐substrate ionization and touch ionization.…”
Section: Introductionmentioning
confidence: 99%
“…Although the modification implies several advantages, bare biosorbents simplify and speed up the workflow and reduce the environmental impact related to their preparation. For this purpose, different unmodified biosorbents have been used in microextraction [12][13][14][15]. However, they require a previous cleaning to remove impurities or intrinsic components that may interfere in the instrumental determination of the target compounds [16,17].…”
Section: Introductionmentioning
confidence: 99%